Perturbations of Ubiquitin-Proteasome-Mediated Proteolysis in Aging and Alzheimer’s Disease - Hegde, Ashok N.; Smith, Spencer G.; Duke, Lindsey M.; Pourquoi, Allison; Vaz, Savannah (Frontiers in Aging Neuroscience, 2019)
The ubiquitin-proteasome pathway (UPP) has multiple roles in the normal nervous system including development of synaptic connections and synaptic plasticity. Research over the past several years has indicated a role for the UPP in aging without any overt pathology in the brain. In addition, malfunction of the UPP is implicated in Alzheimer’s disease (AD) and dementia associated with it. In this review, we assess the literature on the role of protein degradation by the UPP in aging and in AD with special emphasis on dysregulation of the UPP and its contribution to cognitive decline and impairment.